Esthetic and palliative management of congenitally missing anterior teeth using all ceramic fixed prosthesis: A clinical case report - Karthik Kannaiyan; Veerendra Prasad; V Bhanu Chander; Ramavarapu Avinash; Afreen Kouser (Wolters Kluwer Medknow Publications, 2021)
Congenitally missing anterior teeth alters the patient's physiognomy and diction in a big way. Maxillary incisor agenesis, prominently the lateral incisor is the most common congenitally missing permanent tooth, in the anterior maxillary region, which is the esthetic zone, representing approximately 20% of all dental anomalies. Treatment planning is inclusive of; smile design, preparation, perception of the patients, and their expectations in relation to esthetics, interdisciplinary alliance that meets the functional, health, and esthetic needs. A critical factor for the overall success is that of choosing a suitable restorative recourse. The case report describes the esthetic rehabilitation for congenitally missing maxillary lateral incisor and early traumatic loss of central incisor using an all ceramic-fixed prosthesis.